Do Schools Affect Unsafe Sexual Behaviors among High School Students in Boyolali, Central Java? A Multilevel Analysis Approach - Bela Novita Amaris Susanto; Ismi Dwi Astuti Nurhaeni (Journal of Health Promotion and Behavior, 2018)
Background: Premarital sexual behavior is a multidimensional problem, which is influenced by various factors, one of them in school. The majority of adolescents engage in risky sexual behavior the first time when they are in high school, namely at the age of 15-18 years. The purpose of this study was to analyze the influence of schools on unsafe sexual behavior in high school students in Boyolali, Central Java.Subjects and Method: This was an across-sectional study conducted in senior high schools in Boyolali, Central Java, from October to November 2018. A total of 200 students was selected by cluster random sampling. The dependent variable was unsafe sexual behavior. The independent variables were knowledge, attitude, self-efficacy, understanding of the region, parental supervision, access to information, and subjective norm. The data were collected using questionnaire and data were analyzed using multilevel logistic regression.Results: Premarital sexual behavior decreased with high knowledge (b= -3.33; 95% CI= -5.88 to - 0.79; p= 0.010), positive attitude (b= -5.16; 95% CI= -8.63 to -1.70; p= 0.004), strong self-efficacy (b = -4.65; 95% CI = -7.37 to -1.94; p = 0.001), good understanding of religion (b= -3.95; 95% CI = -6.82 to -1.10; p= 0.007), strict parental supervision (b= -3.70; 95% CI= -6.60 to -0.80; p= 0.012), good access to information (b = -3.61; 95% CI = -6.10 to -1.12; p = 0.004), and subjective norm (b = -2.43; 95% CI= -4.60 to -0.25; p= 0.029). Schools had negligible contextual effect on premarital sexual behavior with ICC <0.1%.Conclusion: Premarital sexual behavior decreases with high knowledge, positive attitude, strong self-efficacy, a good understanding of religion, strict parental supervision, high exposure to information access, and subjective norm. Schools have a negligible contextual effect on premarital sexual behavior.Keywords: unsafe sexual behavior, senior high school, multilevel analysisCorrespondence: Bela Novita Amaris Susanto. Masters Program in Public Health. Universitas Sebelas Maret, Jl. Ir. Sutami No.36 A, Surakarta 57126, Central Java. Email: bnamaris@gmail.com. Mobile: +6285788844440.Journal of Health Promotion and Behavior (2018), 4(2): 230-239https://doi.org/10.26911/thejhpb.2018.03.04.02